Mechanical and ballistic properties of coir composite panel - Affandi, Nuraishah Bazilah (2012)
The focus of the study about randomly-woven coir sheets is to determine its potential as a kinetic energy absorber with the aim of implementing the sheet as an impact-worthy constituent. Among the effects of this study are the extension in the service life of raw coir, nomination of coir sheet as a competitive alternative to conventional materials and contribution towards the knowledge of coir in the continuous form as other studies tend to focus on coir in the discontinuous form. Tensile tests using a universal testing machine to determine the mechanical properties and ballistic impact tests using a light-gas gun and high-speed camera to determine the energy absorption properties were performed on fabricated specimens. The coir/epoxy composite specimen consisted of coir sheets layered together with epoxy resin minimally applied to adjacent exterior sheet surfaces,thus leaving the core of the sheet practically partially hollow, where the weight of the sheets and thickness of the resin were controlled. Through this work, a 1-layer of this composite behaves in a brittle fashion and has a modulus and tensile strength of 93.85 MPa and 2.77 MPa, respectively. The 2-layer and 3-layer behaves in a ductile fashion and has a modulus and tensile strength of 46.99 MPa and 1.77 MPa, and 40.07 MPa and 2.70 MPa, respectively. The relation between the number of layers and absorbed kinetic energy has too been discovered for this particular composite to be f(x) = 12:62x -0:02. To totally stop a projectile moving at 205 m/s, it has been found that a 10-layer composite (with a dimension of 100 mm (L) X 100 mm (W) X 8 mm (T) and weighing 12 g per sheet) of this fiber is needed.